Same day ART initiation versus clinic-based pre-ART assessment and counselling for individuals newly tested HIV-positive during community-based HIV testing in rural Lesotho – a randomized controlled trial (CASCADE trial). (December 2016) - Labhardt, Niklaus; Ringera, Isaac; Lejone, Thabo; Masethothi, Phofu; Thaanyane, T'sepang; Kamele, Mashaete; Gupta, Ravi; Thin, Kyaw; Cerutti, Bernard; Klimkait, Thomas; Fritz, Christiane; Glass, Tracy
Abstract Background Achievement of the UNAIDS 90-90-90 targets in Sub-Sahara Africa is challenged by a weak care-cascade with poor linkage to care and retention in care. Community-based HIV testing and counselling (HTC) is widely used in African countries. However, rates of linkage to care and initiation of antiretroviral therapy (ART) in individuals who tested HIV-positive are often very low. A frequently cited reason for non-linkage to care is the time-consuming pre-ART assessment often requiring several clinic visits before ART-initiation. Methods This two-armed open-label randomized controlled trial compares in individuals tested HIV-positive during community-based HTC the proposition of same-day community-based ART-initiation to the standard of care pre-ART assessment at the clinic. Home-based HTC campaigns will be conducted in catchment areas of six clinics in rural Lesotho. Households where at least one individual tested HIV positive will be randomized. In the standard of care group individuals receive post-test counselling and referral to the nearest clinic for pre-ART assessment and counselling. Once they have started ART the follow-up schedule foresees monthly clinic visits. Individuals randomized to the intervention group receive on the spot point-of-care pre-ART assessment and adherence counselling with the proposition to start ART that same day. Once they have started ART, follow-up clinic visits will be less frequent. First primary outcome is linkage to care (individual presents at the clinic at least once within 3 months after the HIV test). The second primary outcome is viral suppression 12 months after enrolment in the study. We plan to enrol a minimum of 260 households with 1:1 allocation and parallel assignment into both arms. Discussion This trial will show if in individuals tested HIV-positive during community-based HTC campaigns the proposition of same-day ART initiation in the community, combined with less frequent follow-up visits at the clinic could be a pragmatic approach to improve the care cascade in similar settings. Trial registration NCT02692027, registered February 21, 2016